An Analysis of the Hanyu Pinyin Errors of the Indonesian Students - Fu Ruomei (Bina Nusantara University, 2013)
Pinyin is a valuable tool for students who learn Chinese as a second language. Through years of teaching practice and observation, some errors in Indonesian students’ understanding and using in Pinyin were summed up, includingthe phonetic alphabet equated to the actual voice entirely caused the mispronunciation; lack of understanding in some special provisions in Pinyin caused the confusion of vowels “u” and “ü”; improperly placement of tone marks; did not understand the pinyin word-segmentation resulting in memory and understanding of Chinese based on Chinese characters instead of the word as a unit. These errors disturbed the accuracy of Chinese students’ pronunciation, caused problems in Chinese vocabulary understanding. It is very important for Indonesian Chinese language learners to lay a solid foundation of Pinyin and develop good habits in the use of Pinyin.